2018
DOI: 10.7759/cureus.3546
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Sheath Diameter Assessment in Patients with Intracranial Pressure Monitoring

Abstract: BackgroundOptic nerve sheath diameter (ONSD) has been found to have good correlation with intracranial pressure (ICP) measurements. Here, we aim to determine if the correlation between ONSD and ICP persists throughout the acute phase of neurologic injury through the evaluation of patients with ICP monitoring. We also aim to determine if the ONSD assessments at different depths (3, 6, or 9 mm) and a ratio of the ONSD and eyeball transverse diameter (ETD) are better correlated with ICP than the well-studied ONSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Conversely, the ONSD/ETD ratio was first described in 2014 and seemed to be more accurate in predicting ICP than ONSD alone [ 8 , 9 ]. A number of scholars have demonstrated that ONSD increases with the elevation of ICP, and increased ICP is strongly correlated with the poor prognosis of patients with neurological disorders [ 7 , 10 12 ]. It was found that ONSD was increased in 95% of patients with ICH or SAH, as indicated by CT, and ONSD was 6.6 ± 0.8 mm with a cut-off value of 5.5 mm, suggesting an elevated ICP [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the ONSD/ETD ratio was first described in 2014 and seemed to be more accurate in predicting ICP than ONSD alone [ 8 , 9 ]. A number of scholars have demonstrated that ONSD increases with the elevation of ICP, and increased ICP is strongly correlated with the poor prognosis of patients with neurological disorders [ 7 , 10 12 ]. It was found that ONSD was increased in 95% of patients with ICH or SAH, as indicated by CT, and ONSD was 6.6 ± 0.8 mm with a cut-off value of 5.5 mm, suggesting an elevated ICP [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a noninvasive monitoring method of ICP, ONSD has been used for 20 years and expected to be an effective technique to predict the prognosis of patients. Some researches suggest that ONSD increases with the increase of intracranial pressure, and the increase of ICP has a signi cant correlation with the poor prognosis of neurological function [7,[10][11][12]. It was found that ONSD increased in 95% of patients with CT indicated ICH or SAH, and the pathological ONSD was 6.6 ± 0.8 mm, ONSD/ETD ratio was 0.29 ± 0.05 against normative 0.19 ± 0.02.…”
Section: Discussionmentioning
confidence: 99%
“…There are different methods of performing this test, but I think that the most accurate fIgUre 12. Aorta width measurement and the fastest method is the 3-point compression method [43].…”
Section: Deep Vein Thrombosis Dvtmentioning
confidence: 99%